A Quest for the 'New Man' in Times of Transition: Faith, Unfaith and the Pitfalls of Utopia in JM Coetzee's The Master of Petersburg. Issue 2 (2nd July 2016) - Dimitriu, Ileana
Abstract : I offer a re-reading of JM Coetzee's novel, The Master of Petersburg (1994 ), according to which I seek to answer the question: Why return to this particular novel today? In pursuing the question, I accord a greater directness than hitherto to both religious and political reference. My point is to locate the novel, both locally and internationally, in a current climate of religious-cum-political demagoguery and conviction. I argue that, in retrospect, we may appreciate Coetzee's uncanny prescience: a vision that evokes the temper of the world today. Central to my analysis is the figure of the 'new man'; forged in radicalised political times and treading a precarious path between faith and unfaith, utopia and delusion, revolutionary fervour and collective amnesia.